Evaluation of indigenous fungal entomopathogens and aqueous leaf extract of Annona muricata against Polyphagotarsonemus latus infesting Jatropha curcas in Indonesia - Retno Dyah Puspitarini; AMINUDIN AFANDHI; ITO FERNANDO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Puspitarini RD, Afandhi A, Fernando I. 2021. Evaluation of indigenous fungal entomopathogens and aqueous leaf extract of Annona muricata against Polyphagotarsonemus latus infesting Jatropha curcas in Indonesia. Biodiversitas 22: 2648-2655. The broad mite Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae) has been known to cause a great deal of injury on Jatropha curcas (L.) plantation in Indonesia. Isolation of indigenous fungal entomopathogens from rhizosphere soils, followed by pathogenicity assay was conducted to find an effective isolate for controlling P. latus. Additionally, the potential combination of the selected isolate and soursop (Annona muricata L.) aqueous leaf extract (SLE) was investigated. A total of 24 isolates were obtained by using the insect bait method. Four fungal isolates, namely Paecilomyces sp. 1., Lecanicillium sp., Beauveria sp., and Fusarium sp. 1, showed high conidial viability and were chosen as representatives to assess their pathogenicity against P. latus. Among the tested isolates, Beauveria sp. which had the highest conidial viability among the tested isolates, needed a shorter period to completely kill the tested mites. However, the compatibility test revealed the deleterious effect of SLE on Beauveria sp. SLE at all concentrations showed a very toxic effect on the fungus, therefore the two must be applied separately. Our results provide useful information on the effectiveness of indigenous entomopathogenic fungi Beauveria sp. and aqueous leaf extract of A. muricata as an alternative tool to control the broad mite P. latus on the J. curcas plantation.